CHOICE - Directed Study: Consequences of longterm- Confinement and Hypobaric HypOxia on Immunity in the Antarctic Concordia Environment - Mehta, Satish; Feurecker, matthias; Pierson, Duane; Sams, Clarence; Quiriarte, Heather; Chouker, Alexander; Stowe, Raymond; Crucian, Brian; Salem, Alexander (2010)
Concerning ground-based space physiological research, the choice of analog must carefully match the system of interest. For spaceflight-associated immune dysregulation (SAID), Antarctica winter-over has emerged as potentially the best terrestrial analog. The prolonged mission durations, extreme/dangerous environment, station-based lifestyle, isolation from outside world, disrupted circadian rhythms, and other psychological aspects make this analog extremely high fidelity for exploration-class space missions (long duration lunar, Mars). NASA, ESA and RSA are currently investigating SAID, with NASA currently operating the Integrated Immune flight study. It is desirable to have a ground analog for SAID validated, so that potential countermeasures might be validated terrestrially prior to during flight. For this presentation, NASA data collected on the winterover 2009 crewmembers, baseline through early deployment will be presented. Through early deployment (approximately 2-3 weeks at Concordia), phenotypic alterations included increased levels of memory T cells, shifts among the CD8+ T cell compartment to a more mature phenotype, and increases in constitutively activated T cells. CD8+/IFNg+ T cell percentages, and T cell blastogenesis functional responses were depressed early deployment as compared to healthy controls. In four compatible subjects, secreted T cell Th1/Th2 cytokines were measured following culture stimulation, and a Th2 shift was observed as compared to controls. Post-winter over frozen sample return will be required to determine if this shift persisted during the winter over period. Additionally, circadian rhythms remained altered compared to baseline, as determined through 5x daily cortisol measurements. Latent viral reactivation will not be determined until frozen sample return occurs.